2017
DOI: 10.1016/j.rbmo.2017.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Timing therapeutic donor inseminations in natural cycles: human chorionic gonadotrophin administration versus urinary LH monitoring

Abstract: This cohort study assessed whether timing therapeutic donor sperm inseminations (TDI) in natural cycles (NC) using ultrasound monitoring and ovulation trigger with human chorionic gonadotrophin (US/HCG) improves cumulative live birth rates (LBR) compared with detection of LH surge with urinary kits (u-LH). It included 232 normo-ovulatory women aged ≤40 years, undergoing 538 TDI in NC between 2011 and 2014. In the u-LH group (113 women, 267 cycles), TDI was performed the day following a positive test. In the US… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…In normo-ovulatory women, IUI may be performed either with a spontaneous LH surge or with a human Chorionic Gonadotropin (hCG) ovulation trigger. Spontaneous LH surge measured in the urine has been compared to administration of an hCG trigger in natural cycles in a retrospective study [ 85 ] and to CC-stimulated cycles in a randomized study [ 86 ]. Both studies found comparable pregnancy rates with urinary LH measurement versus use of an hCG trigger.…”
Section: How Do Cycle Factors Affect Pregnancy Outcomes?mentioning
confidence: 99%
“…In normo-ovulatory women, IUI may be performed either with a spontaneous LH surge or with a human Chorionic Gonadotropin (hCG) ovulation trigger. Spontaneous LH surge measured in the urine has been compared to administration of an hCG trigger in natural cycles in a retrospective study [ 85 ] and to CC-stimulated cycles in a randomized study [ 86 ]. Both studies found comparable pregnancy rates with urinary LH measurement versus use of an hCG trigger.…”
Section: How Do Cycle Factors Affect Pregnancy Outcomes?mentioning
confidence: 99%
“…A retrospective cohort study by El Hachem et al found no difference in clinical pregnancy or live birth rates between urinary LH monitoring vs. hCG-triggered ovulation in natural unstimulated therapeutic donor sperm insemination cycles ( 11 ). The inclusion criteria of that study were strict: only normo-ovulatory women were included.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple clinical studies have assessed the effect of hCG on pregnancy outcomes, but have reached inconsistent conclusions (9)(10)(11)(12). Such conflicting results result from clinical indication, female age, baseline characteristics of study participants, sperm quality, timing, or type of ovarian stimulation.…”
Section: Introductionmentioning
confidence: 99%
“…The timing of insemination is a key factor affecting the outcome after IUI-D [18]. A proper interval from insemination to ovulation (I-O interval) may increase the chance of pregnancy [19]. Several studies have investigated the effects of different insemination time on the pregnancy rate (PR) but have reported inconsistent conclusions [20][21][22].…”
Section: Introductionmentioning
confidence: 99%